A Perovskite Nanorod as Bifunctional Electrocatalyst for Overall Water Splitting - Zhu, Y. (WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim., 2017)
The development of highly efficient and low-cost electrocatalysts for oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) is paramount for water splitting associated with the storage of clean and renewable energy. Here, this study reports its findings in the development of a nanostructured perovskite oxide as OER/HER bifunctional electrocatalyst for overall water splitting. Prepared by a facile electrospinning method, SrNb0.1Co0.7Fe0.2O3-d perovskite nanorods (SNCF-NRs) display excellent OER and HER activity and stability in an alkaline solution, benefiting from the catalytic nature of perovskites and unique structural features. More importantly, the SNCF-NR delivers a current density of 10 mA cm-2 at a cell voltage of merely ˜1.68 V while maintaining remarkable durability when used as both anodic and cathodic catalysts in an alkaline water electrolyzer. The performance of this bifunctional perovskite material is among the best ever reported for overall water splitting, offering a cost-effective alternative to noble metal based electrocatalysts.